"The Impact Of Change Management On Organization Re- Structure: Strategic – Perspective" (Al-Mansour Journal, 2022)
More argument conversations are those that revolve around organizational structures building, and when talking about the formulation of goals, it should firstly talked about the strategic vision and mission, because these concepts are derived from goals. Organization needs the efficiently means especially when an environment is characterized by complexity and uncertainty to adapt and make certainty and stability state within the organization. The research studies the impact of change management on organizational Re- structure in term of recent concepts that taken by organizational consideration literatures such as the organizational strategy, total quality management, and Re- engineering management. Environmental change is one of the most important challenges which face organizations today, and in order to keep the organization in intense competition, it must develop goals according with the requirements of customer satisfaction, and needs to build flexible structures responding to each change situation. The pioneers of organizational literatures emphasis on fact that the searching on the subject of goals should be associated with searching about system of values of the organization, which include a set of beliefs, culture and organizational philosophy, which lead all organizational member for unit direction then convert these concepts to the rules of behaviors for working. The research sets unique mix these recent concepts in term of relationship study the re- structure process with goals developing process according with continues change goals that represent the customer satisfaction